The Existence of Legal Aid Institutions as Embodiments of Principle of Equality Before the Law - Arhjayati Rahim; Noor Asma; Astika Hunawa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
This study discusses the existence of Legal Aid Institutions in providing legal assistance, and the implementation of the provision of legal assistance to the community so as to realize the principle of equality before the law. Research locus was conducted in South Sulawesi Province (LBH Makassar, PBHI) and in Gorontalo Province (LBH FSE Sultan Amai Gorontalo IAIN, LBH Ichsan, YLBHI). The results showed that the existence of Legal Aid Institutions can provide satisfaction and a positive response from the community who consider that when dealing with the law it must be expensive but with the existence of legal aid institutions the poor can get free legal services at no cost, but there are still many poor who do not yet know about the existence of facilities and containers provided by the State in terms of providing free legal assistance. The implementation of legal assistance which is the goal of legal aid agencies for the poor has been carried out well even though in the field implementation many obstacles have been encountered in maximizing legal aid services at the research sites.